Black Elk speaks - Black Elk, 1863-1950 (University of Nebraska Press, 2014)
"Black Elk Speaks, the story of the Oglala Lakota visionary and healer Nicholas Black Elk (1863-1950) and his people during momentous twilight years of the nineteenth century, offers readers much more than a precious glimpse of a vanished time. Black Elk's searing visions of the unity of humanity and Earth, conveyed by John G. Neihardt, have made this book a classic that crosses multiple genres. Whether appreciated as the poignant tale of a Lakota life, a history of a Native nation, or an enduring spiritual testament, Black Elk Speaks is unforgettable"--